Aged dissolved organic carbon exported from rivers of the Tibetan Plateau - Qu, Bin; Sillanpää, Mika; Li, Chaoliu; Kang, Shichang; Stubbins, Aron; Yan, Fangping; Aho, Kelly Sue; Zhou, Feng; Raymond, Peter A. (PLOS ONE, 2017)
The role played by river networks in regional and global carbon cycle is receiving increasing attention. Despite the potential of radiocarbon measurements (14C) to elucidate sources and cycling of different riverine carbon pools, there remain large regions such as the climate-sensitive Tibetan Plateau for which no data are available. Here we provide new 14C data on dissolved organic carbon (DOC) from three large Asian rivers (the Yellow, Yangtze and Yarlung Tsangpo Rivers) running on the Tibetan Plateau and present the carbon transportation pattern in rivers of the plateau versus other river system in the world. Despite higher discharge rates during the high flow season, the DOC yield of Tibetan Plateau rivers (0.41 gC m-2 yr-1) was lower than most other rivers due to lower concentrations. Radiocarbon ages of the DOC were older/more depleted (511±294 years before present, yr BP) in the Tibetan rivers than those in Arctic and tropical rivers. A positive correlation between radiocarbon age and permafrost watershed coverage was observed, indicating that 14C-deplted/old carbon is exported from permafrost regions of the Tibetan Plateau during periods of high flow. This is in sharp contrast to permafrost regions of the Arctic which export 14C-enriched carbon during high discharge periods.
Keywords: Carbon cycle; Carbon dioxide; Climate change; Rain; Rivers; Surface water; Tibetan people; TIBETAN PLATEAU